0
$\begingroup$

I am struggling with that exercise... i don't understand a step in the answer. Maybe somebody Can explain in here or at least give me a hint what's going on there.

$a_{n} = \frac{7*(n+2)}{2*n} *a_{n-1}$ ,$a_{1} = 14$

So it's...

$a_{2} = \frac{7*4}{4} * a_{1} = \frac{7*4 * 14}{4} = \frac{2* 7^{2}*4 }{4}$

$a_{3} = \frac{7*5}{6} * a_{2} = \frac{2* 7^{3}*4*5 }{4*6}$

And here is the problem... a4 equals:

$a_{4} = \frac{7*6}{8} * a_{3} = \frac{2* 7^{4}*4*5*6 }{4*6*8}$

We are multiplying numerator and denominator with 2*3 to get factorial 6! on numerator. I can't understand how the $(1*2*3)^2$ got on denominator and how after that we transformed it to $3! * 4!$. Next steps are quite easy and the mathematical induction is fully understandable for me.

$a_{4} = \frac{2* 7^{4}*6! }{ (1*2*3)^{2} * 2 *3 *4 } = \frac{2* 7^{4}*6! }{ 3! 4! }$

Full answer of the exercise: JPG image

$\endgroup$
0
$\begingroup$

Your doubt is valid: $$\begin{align}a_{n}& = \frac{7*(n+2)}{2*n} *a_{n-1}, a_1=14\\ a_2&=\frac{7*4}{4}*a_1=\frac{2*7^2*4}{4}=\frac{2*7^2*4!}{4!}\\ a_3&=\frac{7*5}{6}*a_2=\frac{2*7^3*4*5}{4*6}=\frac{7^3*5!}{2*3!*3!}\\ a_4&=\frac{7*6}{8}*a_3=\frac{7^4*5!*6}{2*3!*3!*8}=\frac{7^4*6!}{2^2*3!*4!}\\ a_5&=\frac{7*7}{10}*a_4=\frac{7^5*6!*7}{2^2*3!*4!*10}=\frac{7^5*7!}{2^3*3!*5!}\\ \vdots\\ a_n&=\frac{7^n*(n+2)!}{2^{n-2}*3!*n!},n\ge 1.\end{align}$$ Verify: $$\begin{align}a_1&=\frac{7^1*(1+2)!}{2^{1-2}*3!*1!}=14\\ a_2&=\frac{7^2*(2+2)!}{2^{2-2}*3!*2!}=2*7^2\\ a_3&=\frac{7^3*(3+2)!}{2^{3-2}*3!*3!}=\frac{7^3*5!}{2*3!*3!}\end{align}$$

$\endgroup$
  • $\begingroup$ Thank u a lot. Now is everything clear! Thanks once again :) $\endgroup$ – Jim.D Mar 21 at 14:10
  • $\begingroup$ You are welcome. If you think it answers your question, you can accept it. Good luck $\endgroup$ – farruhota Mar 21 at 14:24
0
$\begingroup$

I got $$a_n=\frac{2}{3}\frac{7^n}{2^n}(n+1)(n+2)$$

$\endgroup$
0
$\begingroup$

$$a_n=a_{n-r}\cdot\dfrac{7^r(n+2)(n+1)\cdots(n-r+3)}{2^r n(n-1)\cdots(n-r+1)}$$ $0\le r\le n-1$

For $r\ge2\implies n\ge3$ $$a_n=a_{n-r}\cdot\left(\dfrac72\right)^r\dfrac{(n+2)(n+1)}{(n-r+2)(n-r+1)}$$

Set $r=n-1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.